2023
DOI: 10.3390/polym15020309
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Fly Ash-Slag Based Geopolymer for Repair of Road Subgrade Diseases

Abstract: Fly ash-slag-based geopolymer is a grouting material with good fluidity and excellent mechanical and eco-friendly properties. The geopolymer can react chemically with the inert minerals of road subgrade under alkali excitation to form a good interfacial bond between road subgrade; therefore, it is suitable for the repair of weak road sections. In order to solve the problems such as the difficulty to store and transport the liquid activator of existing geopolymer grouting materials and to study the unclear mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…With continued research, it is likely that nanosilica-modified geopolymer matrices will become even more versatile and cost-effective, making them a promising alternative to traditional cement-based materials. Overall, the addition of nanosilica to geopolymer matrices shows great promise for enhancing the properties and expanding the potential applications of these inorganic materials [115,116].…”
Section: Geopolymer Nanocomposites Reinforced With Nanosilicamentioning
confidence: 99%
“…With continued research, it is likely that nanosilica-modified geopolymer matrices will become even more versatile and cost-effective, making them a promising alternative to traditional cement-based materials. Overall, the addition of nanosilica to geopolymer matrices shows great promise for enhancing the properties and expanding the potential applications of these inorganic materials [115,116].…”
Section: Geopolymer Nanocomposites Reinforced With Nanosilicamentioning
confidence: 99%
“…This review researches various methodologies for subgrade defect detection, data processing, and modeling analysis. Notably, owing to minimal traffic impact and difficulty associated with large-scale detection of shoulder areas, research on shoulder defects remains relatively scant, with a predominant reliance on manual inspection [12]. In alignment with the composition of the subgrade, this paper classifies subgrade defects into categories such as embankment and subgrade distresses, drainage facility distresses, subgrade slope distresses, and deficiencies in existing protective and retaining structures.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the way to improve the mechanical properties of geopolymer materials under ambient curing conditions is generally to add materials with high CaO content, such as slag [ 23 , 24 ], Portland cement [ 25 ] or Ca(OH) 2 [ 6 ], but these methods have corresponding imperfections. For example, previous studies found that adding slag will significantly shorten the setting time of concrete and affect workability.…”
Section: Introductionmentioning
confidence: 99%